34. EVALUATION OF THE SAFETY OF STEMSUP AEROSOL THERAPY IN PATIENTS WITH CHRONIC OBSTRUCTION PULMONARY DISEASE (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and paraclinical characteristics and initially evaluate the safety of Stemsup aerosol therapy in patients with chronic obstructive pulmonary disease. Materials and Methods: This is an interventional, open-label, single-group study on 30 patients with COPD groups C and D treated at the Tuberculosis and Lung Disease Department of Military Hospital 175 from 8/2021 - 12/2023. Results: 100% of patients were male, with an average age of 67.5 ± 6.9 years old. The average mMRC score was 2.23 ± 0.57. 6MWT is 326.7 ± 88.2 m. The average CAT score was 18.1 ± 4.9 points. The average BODE score is 4.33 ± 1.62, of which BODE III accounts for the highest percentage (40%),and the lowest is BODE IV accounting for 10%. The average values of lung ventilation indicators in the studied patients all decreased compared to LLN, in which FEV1(%LLN) decreased significantly (45.1 ± 14.9%LLN). Side effects only occurred in 1 case of increased difficulty breathing, accounting for 3.3%. 13.3% of patients had a mild and transient increase in CRP after 1 month of Stemsup aerosol therapy. There were no cases of serious complications after using Stemsup. Conclusion: Stemsup aerosol therapy in COPD patients was well tolerated without significant serious side effects. This is a promising method for the treatment of COPD patients.
Keywords: Chronic obstruction pulmonary disease, stemsup, safety.